Evaluation of In-Barn Feeder Management Prior to Marketing to Reduce Feed Cost, Improve Carcass Yield, and Impact on Economic Return - Hilario M. Cordoba; Joel M. DeRouchey; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 695 mixed sex growing-finishing pigs (600 × 241, DNA; initially 242.7 ± 1.36 lb) were used in a 14-d trial to determine the effects of feed withdrawal before the first and final marketing event on carcass weight, carcass yield, and economics. Pens of pigs were assigned to 1 of 3 treatments in a randomized complete block design. There were 24 pens per treatment and 9 or 10 pigs per pen. Treatments consisted of none, 6, or 12 h of feeder closure prior to loading pigs on the truck at both the first (2 weeks before final marketing) and final marketing to achieve approximately 12, 18, and 24 h of feed withdrawal prior to harvest at the processing plant. There was no evidence of differences (P≥ 0.10) for ADG, ADFI, or F/G during the 14-d period between the first and final marketing event. However, pig BW at time of loadout, with 24-h of feed withdrawal prior to harvest were lighter (P<0.05) than those with only 12 h of feed withdrawal both at first marketing event and the last. Pigs that had access to feed (12 h withdrawal prior to harvest) gained weight during the marketing day, while pigs with 18 or 24 h of feed withdrawal lost weight. For carcass characteristics, pigs at final marketing with 12 h feed withdrawal prior to harvest had increased (P<0.05) HCW compared to those with 24 h feed withdrawal. There was a tendency (P= 0.055) for a treatment effect with pigs undergoing 12 h feed withdrawal prior to harvest having a 1.1 lb heavier HCW than those with 24 h feed withdrawal. When evaluating carcass yield, using live weights for all pigs 24 h prior to harvest, pigs in the final marketing group with 12 h of feed withdrawal prior to harvest had greater yield (P<0.05) than those marketed with 24 h of feed withdrawal. However, when evaluating carcass yield using live weights 12 h prior to harvest for the final marketing and overall, pigs marketed at 24 h of feed withdrawal had greater yield (P<0.05) than the other two treatments. Conversely, in the first marketing event, pigs with 12 h of feed withdrawal had decreased yield compared to pigs with the 18 and 24 h of feed withdrawal treatment. There were no differences in backfat, loin depth, and lean % between treatments. Feed consumed on the day of marketing and feed cost per pig were increased (P<0.05) for pigs marketed with 12 or 18 h of feed withdrawal prior to harvest compared to those with 24 h feed withdrawal. In conclusion, there were no differences between the treatments on HCW and carcass yield at the first marketing event. However, in the final marketing event, differences were observed between the 12 h feed withdrawal prior to harvest and 24 h feed withdrawal prior to harvest treatments on HCW and carcass yield. Carcass yield was greatest for those with 12 h of feed withdrawal prior to harvest at the final marketing event. Also, as expected, pigs with a longer time of feed withdrawal had reduced feed consumption and feed cost/pig on the day of marketing. Thus, saving in feed cost would have to offset the reduction in carcass weight value to justify withholding feed for greater than 12 h prior to harvest.
Keywords: finishing pigs; carcass characteristics; feed withdrawal